Analisis Stabilitas Pondasi Terhadap Rembesan Dan Piping Pada Bendungan (Studi Kasus Bendungan Jragung Kabupaten Semarang) - Riko Bagus Setiyawan; Rekhan Farras Sutrisno; Abdul Rochim; Lisa Fitriyana; Ahmad Hidayawan (Jurnal Civil Engineering Study, 2025)
The dam foundation is a basic structure that meets the requirements as a supporting sector for dam construction and ensures safety against one of the serious threats in the form of seepage and Piping. Therefore, analyzing the stability of the dam foundation against seepage and Piping is necessary. This study uses the Finite Element program to analyze stability, seepage, and Piping under Normal Water Level conditions. Dam stability analysis is carried out by adding earthquake load coefficient factors OBE (Operating Basis Earthquake) and MDE (Maximum Design Earthquake). The analysis is carried out in two stages, namely the first stage without additional repairs and the second stage with additional repairs in the form of Curtain Grouting and Cut-off wall. Under Normal Water Level conditions without earthquakes or with OBE and MDE 1.00H earthquakes, the stability of the foundation in Existing conditions, Alternative 1, and Alternative 2 meets the criteria, but does not meet the MDE 0.25H, 0.50H, and 0.75H earthquakes so that dynamic analysis is required using the Makdisi-Seed method. Seepage analysis shows that the discharge in the Existing condition is 49,716.74 m³/day exceeding the permit limit of 45,000 m³/day, while Alternative 1 (255.13 m³/day) and Alternative 2 (238.55 m³/day) meet the criteria. Meanwhile, Piping analysis in Normal Water Level conditions shows that the Existing does not meet the Safety Factor, while Alternative 1 and Alternative 2 meet the criteria and are safe for Piping.